A comparison of anthropometric and training characteristics of Ironman triathletes and triple Iron ultra-triathletes - Knechtle, B.; Knechtle, P.; Rüst, C. A.; Rosemann, T. (Journal of Sports Sciences, 2011)
We examined differences in anthropometry and training between 64 Triple Iron ultra-triathletes competing over 11.4 km swimming, 540 km cycling, and 126.6 km running, and 71 Ironman triathletes competing over 3.8 km swimming, 180 km cycling, and 42.2 km running. The association of anthropometry and training with race time was investigated using multiple linear regression analysis. The Triple Iron ultra-triathletes were smaller (P < 0.05), had shorter limbs (P < 0.05), a higher body mass index (P < 0.05), and larger limb circumferences (P < 0.01) than the Ironman triathletes. The Triple Iron ultra-triathletes trained for more hours (P < 0.01) and covered more kilometres (P < 0.01), but speed in running during training was slower compared with the Ironman triathletes (P < 0.01). For Triple Iron ultra-triathletes, percent body fat (P = 0.022), training volume per week (P < 0.0001), and weekly kilometres in both cycling (P < 0.0001) and running (P < 0.0001) were related to race time. For Ironman triathletes, percent body fat (P < 0.0001), circumference of upper arm (P = 0.006), and speed in cycling training (P = 0.012) were associated with total race time. We conclude that both Triple Iron ultra-triathletes and Ironman triathletes appeared to profit from low body fat. Triple Iron ultra-triathletes relied more on training volume in cycling and running, whereas speed in cycling training was related to race time in Ironman triathletes.